Assessment of Ionizing Radiation Protection Awareness among Radiation Workers in Erbil Hospitals - Hameed, Safaa Mustafa; Ali, Qasim Ahmad; Ass, Runak Tahir Ali (Journal of medical and pharmaceutical sciences, 2017)
Ionizing radiations are hazardous agents in the workplace and all forms of ionizing radiation produce some type of injury that is incurable. Therefore, application of protection against ionizing radiation exposure can play an important role in the health of workers. The objective of this study is to evaluate the application of radiation protection among radiation workers in x-ray department in Erbil hospitals. Methodology: A cross-sectional study was conducted with six hospitals (General and Private) and samples of 110 workers were randomly selected from among 135 radiation workers. Data was collected through structured questionnaires. The surveyed data was coded and entered into MS Excel software. Further data has been exported to SPSS 18 for analysis. The analysis was performed by means of frequency distributions and cross-tabulations. Results: The results show that there are 47 (42.7%) female and 63 (57.3%) male. A large majority of the workers 51 (46.4%) were aged between 21 - 30 years and Diploma holders 68 (61.8%). Only 49 (44.5%) had undergone primary examination while 47 (42.7%) were never done a periodical examination. According to ICRP regulation of radiation protection, it is mandatory for radiation workers to wear personal detective devices during work. But the majority 89 (80.9%) has not been supplied with such devices. The study also revealed that a large majority of radiation workers are engaged in work beyond 40 hours per week. Calibration of the X-rays machine and radiation survey of the workplace have not been regularly done. Only 30 of the samples have no awareness and knowledge about the ionizing radiation while 95 (86.4%) were said to have no health physicist. Conclusion: Through the study and analysis of the data, it was found that the vast majority of radiations workers in the six hospitals we visited did not have sufficient awareness of the basis of radiation protection and did not comply with the international recommendations for radiation protection.